Primary physical mechanism of different magnetic fields action on roots of some plants - Sheykina, N. V.; Bogatina, N. I. (Biophysical Bulletin, 2017)
Background: Though the magnetic field action on biological object is proved now by many experiments it cannot be explained. The counterarguments are the small value of magnetic induction, that is effective for static magnetic field and the small value of ions free path length for ion cyclotron resonance presence.  Objectives of the article were to generalize all the results that had been obtained before in static, alternative and combined magnetic fields and to explain all results by one and the same primary physical mechanism.Materials and methods that were used to obtain experimental results were based on the using of well reproducible magnetic conditions. For this purpose 3 lays µ-metal shield and superconductive shield with warm volume were used. The artificial magnetic field was created in the shield. The objects of the investigation were roots of cress, maize and pea. Their gravitropic reaction was studied.Results and discussion: All experimental results were compared with the theories and calculations maid before and following from the three mechanisms proposed below. It was shown that there were three physical primary mechanisms that could lead to effect of low frequency alternative and combined magnetic fields and permanent magnetic field on gravitropic reaction in plants. All of them depended on the relative location of roots, gravity and components of permanent and alternative magnetic fields between themselves. The first mechanism is based on the classic model of the rotation of ions in the plane that is perpendicular to the magnetic field direction or precession of magnetic moments round the direction of magnetic field vector. The second mechanism is connected with the piezoelectric properties of starch grain (porous piezoelectricity). This property of starch may create the change in the moving of starch grains in alternative and combined magnetic fields, and even in static one. The third mechanism is caused by the phase transition in water created by weak combined or alternative magnetic fields.Conclusions: The comparison of effects of these three mechanisms between themselves allowed choosing the most possible one. It was shown that the first mechanism was preferred. Only the first mechanism can explain the dependence of observed effects on magnetic field direction.